Role of strontium as doping agent in LaMn0.5Ni0.5O3 for oxygen electro-catalysis - Islam, Mobinul; Jeong, Min-Gi; Oh, In-Hwan; Nam, Kyung-Wan; Jung, Hun-Gi (한국공업화학회, 2020)
Doping is an effective way to trigger various behaviors in ceramics. LaMn0.5Ni0.5O3 perovskites with or without strontium (Sr) doping were prepared using a sol-gel process and characterized by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy (SEM), and BrunauerEmmett-Teller (BET) gas adsorption techniques. A structural transition in the LaMn0.5Ni0.5O3 perovskite was observed upon doping, suggesting its pinning effect on the crystal structure. The SEM and BET results showed that the incorporation of Sr2+ into this oxide material markedly decreased the particle size into the nanoscale range and increased the active surface area. The oxide electrocatalytic properties toward the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in an alkaline medium were measured using a rotating disk electrode. The results revealed that La0.8Sr0.2Ni0.5Mn0.5O3 is a more active catalyst than LaMn0.5Ni0.5O3 for the ORR and OER. The improved electrocatalytic performance of the Sr-doped oxide is related to the increase in ORR/OER current density and the positive shift in the ORR onset potential compared with that of the LaMn0.5Ni0.5O3 catalyst. The overall electron transfer number was measured as approximately 4. The basis of this enhanced performance is discussed in terms of the material electronic structure and morphology. (C) 2020 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.